Validation of a point-of-care clinical chemistry analyser generation of clinical chemistry reference intervals and evaluation of serum protein electrophoresis in the southern white rhinoceros Ceratotherium simum simum - Goddard, Amelia (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.